ANALISIS IMPLEMENTASI PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE (GCG) PADA PT. BANK MANDIRI (PERSERO) TBK. CABANG BENGKULU - Sukandi Andi; Tito Irwanto; Meiffa Herfianti (Unib Press Universitas Bengkulu, 2018)
Abstract: The objective of this research is to Implementation of the good corporate governance (GCG) principles in addition to improving bank competitiveness itself, also provide more protection to the community. The implementation of the good corporate governance (GCG) principles becomes a trust given the banking industry that manages public funds (customers). The objective of this research is to know the analysis implementation of good corporate governance (GCG) principles in PT. Bank Mandiri (Persero) Tbk. Branch of Bengkulu. The object of this research is permanent employee of PT. Bank Mandiri (Persero) Tbk Branch Office of Bengkulu which amounted to 67 people, with sampling method that is total sampling. The sources of data in this study through questionnaires. The data analysis technique used quantitative descriptive analysis with mean method and frequency distribution table. The results of this study research that, implemtasi good corporate governance (GCG) principles at PT. Bank Mandiri (Persero) Tbk. Branch of Bengkulu has been running well with the average value of the statement 3.77 (good). Furthermore, the implementation principles of transparency, accountability, responsibility, independence and fairness have gone well with the average value each statement of 3.71 (good), 3.86 (good), 3.76 (good), 3.67 (good), 3.86 (good).Keyword: governance, bank, competitiveness.